(untitled) (CONFERENCE ON THE ROLE AND IMPORTANCE OF SCIENCE IN THE MODERN WORLD, 2025)
This thesis provides a scholarly examination of the formation and development of postmodernism in contemporary American literature. Emerging in the second half of the twentieth century, particularly after World War II, this literary movement represents a critical evolution of modernism, introducing elements such as metafiction, fragmented narrative, intertextuality, and irony. The study analyzes the aesthetic characteristics, socio-cultural context, and philosophical foundations of postmodernism through the works of authors such as Thomas Pynchon, Don DeLillo, Kurt Vonnegut, Joseph Heller, and David Foster Wallace. Additionally, it evaluates the movement’s impact on American literature, its role in global literary processes, and its legacy in twenty-first-century literature. The findings demonstrate that postmodernism, by integrating literature with mass culture, technology, and consumerism, has blurred the boundaries between reality and fiction, marking a new phase in literary evolution that continues to influence digital literary forms.